The triterpenoids-enriched extracts from Antrodia cinnamomea mycelia attenuate alcohol-induced chronic liver injury via suppression lipid accumulation in C57BL/6 mice - Yange Liu; Ronglong Chen; Lanzhou Li; Ruitao Dong; Hui Yin; Yawen Wang; Anhui Yang; Jianbin Wang; Changtian Li; Di Wang (Food Science and Human Wellness)
The major pathologic hallmark of the alcoholic liver disease (ALD) is the representation of chronic alcohol-induced hepatocyte lipid accumulation. This study aims to investigate the hepatoprotective role of triterpenoids-enriched extracts from Antrodia cinnamomea mycelia (ACT) in chronic alcohol-induced liver injury mice, establishing in C57BL/6 mice through gradient alcohol feeding for 24 weeks. In long-term alcohol consumption mice, the significantly lost body weight, increased organ indexes, hepatic alanine aminotransferase and aspartate aminotransferase levels were all remissed after 6-week ACT orally administration, showing its hepatoprotective property. ACT suppressed the triglyceride, total cholesterol and low-density lipoprotein levels, and enhanced high-density lipoprotein levels in serum or/and liver of chronic alcohol damaged mice. Combining with the pathological observations, ACT displayed an anti-steatosis effects to restrain the progress of ALD. Based on proteomic analysis and enzyme-linked immunosorbent assay, ACT had been confirmed to regulate the levels of lipid biogeneration-related factors and depressed the over-accumulation of hepatic reactive oxygen species. According to further data, ACT prevented alcoholic liver injury may be associated with mediating lipid metabolism-related to PGC-1α and NF-κB signaling. In summary, ACT protected the body against chronic alcohol ingest induced liver injury through its regulation lipid on metabolism.